Barriers to mutational testing in patients with gastrointestinal stromal tumors (GIST) – a survey of life raft group members - Denisse Montoya; Jerry W. Call; Jennily Eshak; Pete Knox; Maeven Luedke; Sahibjeet Kaur; Sara Rothschild; Mary Garland; Norman J. Scherzer (BMC Gastroenterology, 2022)
Abstract Background Due to the low mutational testing rate in patients with Gastrointestinal Stromal Tumors (GIST), The Life Raft Group (LRG), a non-profit organization that provides support, advocacy and conducts research for patients with GIST, analyzed various factors that may have an impact on patients’ ability to receive mutational testing. Methods A survey about mutational testing for patients with GIST or their caregivers, was conducted in June 2020. The survey, sent to 1004 GIST patients and caregivers through email, was promoted through social media with instructions to contact the LRG to participate. The survey was designed by the LRG Patient Registry Department. Members of the LRG, regardless of Patient Registry status, were eligible to participate. Results A total of 295 patients/caregivers participated in this study (response rate: 29.4%). The percentage of patients who indicated they had received mutational testing was much higher in this survey (80%) than in the general GIST community (26.7%). Several reasons were cited for having a test, including: “My doctor ordered/suggested that I have it done” (54%); “The Life Raft Group advised/suggested I have it done” (25%); “I asked my doctor to have it done” (22%); “I had it done as part of a clinical trial” (5%); “I am not sure” (3%) and “Other” (14%). Mutational testing resulted in a treatment change in 25% of cases. Patients were able to select more than one option when completing this question resulting in a percentage greater than 100. Conclusions The LRG membership is voluntary and proactive; patients who join are more likely to participate in surveys and mutational testing, as well as more likely to have a GIST specialist. Mutational testing can influence understanding of a patient’s GIST and the treatment best suited to each case. These are extremely important findings, as it helps ensure that patients are on the proper treatment, which should lead to better outcomes.